Features of direct democracy in Switzerland - Svetlana A. Solomonova (Правоприменение, 2020)
The subject. The article is about the peculiarities of referendum and popular initiative which are the main forms and institutions of direct democracy in Switzerland.The purpose of the article is to determine the peculiarities of direct democracy in Switzerland and characterize its main forms: referendum and popular initiative. In order to achieve the objective the following tasks can be defined: 1) to find the origins and identify the variations of forms of direct democracy in Switzerland; 2) to trace the evolution of enshrining on the statutory level of such institutions of direct democracy in Switzerland as referendum and legislative initiative from the time of their conceiving till the enactment of the actual Constitution; 3) where relevant, to perform a brief comparative analysis of the forms of direct democracy in Switzerland and similar institutions shaped in other countries; 4) to define the role and meaning of referendum and legislative initiative in history as well as in the modern stage of the development of the Swiss State.The methodology of the study includes the use of general scientific methods (description, deduction, induction, analysis and synthesis) together with formal juridical and comparative juridical approach. In addition, throughout the article and, in particular, while working with sources of law, historical approach and systematic approach were practiced. The main results and scope of their application. The article presents the analysis of such forms of direct democracy in Switzerland as referendum and popular initiative, characterizing each form. The principle of democracy expressed by the practice of referendum and legislative initiative is present in its entirety. No country in the world has come as close to applying direct democracy to national political issues as Switzerland. Since the mid-nineteenth century, when the country's first Federal Constitution was adopted, Switzerland has managed to hold more referendums than all other countries combined in the same time frame.Conclusions. Referendum enables Swiss citizens to dismiss the measures taken by their representatives and the initiative gives the citizens possibility to put laws into practice independently from the legislative powers. Swiss experience vividly demonstrates that used sensibly and taking into consideration national legislative traditions such forms of consulting with the people can be quite promising and efficient for other European countries.